2020
DOI: 10.9734/ajee/2020/v12i130152
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistical Modelling of Groundwater Quality at Rumuola Community, Port Harcourt, Nigeria

Abstract: The groundwater quality of Rumuola community of Rivers State, Nigeria was investigated. This study was done to determine the pollution potential of a solid waste open dump in a borrow pit in the community. The leachate pollution index was calculated for the borrow pit at the centre of the community using weighted additive leachate pollution index. The result showed that the LPI value was 5.31 and has low pollution potential. It was discovered that the groundwater in the entire community was acidic with pH leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Bojke (2012) states that productivity is determined by summing the total amount of input and output that was produced. According to Amah(2006), productivity is the amount of resource (input) that is combined and used effectively to produce the long-term, high-quality goods and services that society needs. According to this, efficiency and economical resource usage go hand in hand to produce production.…”
Section: Organizational Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Bojke (2012) states that productivity is determined by summing the total amount of input and output that was produced. According to Amah(2006), productivity is the amount of resource (input) that is combined and used effectively to produce the long-term, high-quality goods and services that society needs. According to this, efficiency and economical resource usage go hand in hand to produce production.…”
Section: Organizational Productivitymentioning
confidence: 99%
“…An organisation with high productivity is one where waste is kept to a minimum and resources are used effectively. Various economic, social, technical, and environmental goals are balanced in terms of productivity (Amah, 2006). Increased profitability for investors and business growth are two benefits of high productivity.…”
Section: Organizational Productivitymentioning
confidence: 99%
“…The physicochemical parameters (pH, EC, TDS, BOD5, COD, TH, SO4, NO3, Turbidity, Pb and PO4) were used to calculate the WQI in this study. The Water Quality Index (WQI) was calculated using the Weighted Average Water Quality Index (WAWQI) method [15,5] which involved:…”
Section: Calculation Of Water Quality Indexmentioning
confidence: 99%
“…Groundwater serves as the main reserve of freshwater and the main sources of water in the urban environment, which is used for drinking, industrial, agricultural and domestic purposes [4]. Groundwater is important to the entire world's population, but more important to semi-arid and arid regions where there is insufficiency of surface water [5].…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the RBF model was the best for interpolation prediction and could ensure the accurate fitting of predicted data with measured data at sampling sites. Based on the relative performance of four interpolation methods, the best methods for interpolating GW quality parameters were Empirical Bayesian Kriging (EBK) for pH, TDS, SO 4 , and NO 3 , and OK for nickel and hardness [39]. Previously, interpolation methods were used to investigate the spatial distribution of NO 3 .…”
Section: Introductionmentioning
confidence: 99%